Factors governing $${\rm H}_{3}^{+}$$ H 3 + formation from methyl halogens and pseudohalogens - Jacob Stamm; Swati S. Priyadarsini; Shawn Sandhu; Arnab Chakraborty; Jun Shen; Sung Kwon; Jesse Sandhu; Clayton Wicka; Arshad Mehmood; Benjamin G. Levine; Piotr Piecuch; Marcos Dantus (Nature Communications)
Abstract The formation of $${\rm H}_{3}^{+}$$ H 3 + following the double ionization of small organic compounds via a roaming mechanism, which involves the generation of H2 and subsequent proton abstraction, has recently garnered significant attention. Nonetheless, a cohesive model explaining trends in the yield of $${\rm H}_{3}^{+}$$ H 3 + characterizing these unimolecular reactions is yet to be established. We report yield and femtosecond time-resolved measurements following the strong-field double ionization of CH3X molecules, where X = OD, Cl, NCS, CN, SCN, and I. These measurements, combined with double-ionization-potential equation-of-motion coupled-cluster ab initio calculations used to determine the geometries and energetics of CH3X2+ dications, are employed to identify the key factors governing the formation of $${\rm H}_{3}^{+}$$ H 3 + in certain doubly ionized CH3X species and its absence in others. We also carry out ab initio molecular dynamics simulations to obtain detailed microscopic insights into the mechanism, yields, and timescales of $${\rm H}_{3}^{+}$$ H 3 + production. We find that the excess relaxation energy released after double ionization of CH3X molecules combined with substantial geometrical distortion that favors H2 formation prior to proton abstraction boost the generation of $${\rm H}_{3}^{+}$$ H 3 + . Our study provides useful guidelines for examining alternative sources of $${\rm H}_{3}^{+}$$ H 3 + in the universe.